THE ANALYSIS OF TURN TAKING STRATEGIES IN EFL CLASSROOMS - Harris Hermansyah Setiajid; Yanuarius Yanu Dharmawan; Nurmala Eka Putri; Susanto Susanto (Universitas Bandar Lampung, 2020)
There are 3 types of turn taking strategies, namely taking the turn, holding the turn and yielding the turn. The purpose of this study is to answer the turn taking used in the classroom with the teacher and students as the participants. This study uses a qualitative approach that analyzes the results of data captured using a video recorder. After recording the data, we do the transcription of the participant conversation based on the recorder. The transcript is based on the theory from Jefferson. Then, to analyze what type of turn taking used by the participants we used Stenstrom theory. Based on the findings in this study, it was concluded that there were several types of turn taking strategies that were not found due to circumstance and timing which were not suitable for use, including 'metacomment' and 'giving up' strategy. From this research it is found that each individual has an original character that builds a conversation with a unique pattern.